2020
DOI: 10.1002/anie.201914264
|View full text |Cite
|
Sign up to set email alerts
|

Functional Nanoparticles with a Reducible Tetrasulfide Motif to Upregulate mRNA Translation and Enhance Transfection in Hard‐to‐Transfect Cells

Abstract: Effective messenger RNA( mRNA) transfection in hard-to-transfect cells delivered by vectors is al ong-standing challenge.N ow it is hypothesizedt hat the high intracellular glutathione level is associated with suppressed mRNAt ranslation. This theory leads to an ew design principle of nextgeneration mRNAv ectors:n anoparticles with glutathione depletion chemistry upregulate mRNAt ranslation and enhance transfection, which is beneficial for mRNAd elivery in hard-to-transfect cells in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 25 publications
0
51
0
7
Order By: Relevance
“… The contribution of nanostructural parameters to mRNA delivery should be reexamined considering the latest findings. For example, the role of tetrasulfide bonds has been revealed to regulate intracellular biochemical reactions and pathways to upregulate mRNA translation [16] . It has been also reported that tetrasulfide bonds contribute to the GSH‐responsive release of cargo [71] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… The contribution of nanostructural parameters to mRNA delivery should be reexamined considering the latest findings. For example, the role of tetrasulfide bonds has been revealed to regulate intracellular biochemical reactions and pathways to upregulate mRNA translation [16] . It has been also reported that tetrasulfide bonds contribute to the GSH‐responsive release of cargo [71] .…”
Section: Discussionmentioning
confidence: 99%
“…An intracellular biochemistry‐guided design principle of mRNA nanocarriers was proposed: nanomaterials with tetrasulfide groups to deplete GSH‐modulated translation in APCs by reducing glyceraldehyde 3‐phosphate dehydrogenase involved translation suppression and activating mTORC1 for upregulated translation activity and enhanced protein expression efficiency (Figure 2 b). [16] To further modulate translation efficiency, efforts may be made to solve the long‐term GSH depletion problem since tetrasulfide bonds in oxidized GSH can be reduced by glutathione reductase in the cellular metabolism. Furthermore, the exploration of other pathways in mRNA translation and cell‐specific biochemistry to impact the level of eIFs may be integrated into material design as possible strategies to modulate translation and achieve more efficient protein expression.…”
Section: Translation Modulators In Mrna Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…b) Nanomaterialien mit reduzierbaren funktionellen Gruppen, um die mRNA‐Translation zu verstärken. Reproduziert mit Genehmigung [16] . Copyright 2020, Wiley‐VCH.…”
Section: Translationsmodulatoren Für Die Mrna‐bereitstellungunclassified
“…Einige Fragen bleiben jedoch offen; 1) Die Auffassung über den Beitrag nanostruktureller Parameter zur mRNA‐Abgabe sollten unter Berücksichtigung der neuesten Erkenntnisse überprüft werden. Beispielsweise die Rolle der Tetrasulfidbindung bei der Regulierung intrazellulärer biochemischer Reaktionen und Signalwege zur Hochregulierung der mRNA‐Translation [16] . Außerdem wurde gezeigt, dass Tetrasulfidbindungen wesentlich an der GSH‐initiierten Freisetzung von Wirkstoffen beteiligt sind [71] .…”
Section: Zusammenfassung Und Ausblickunclassified